2018
DOI: 10.1371/journal.pone.0205514
|View full text |Cite|
|
Sign up to set email alerts
|

Hippo signaling pathway is altered in Duchenne muscular dystrophy

Abstract: Hippo signaling pathway is considered a key regulator of tissue homeostasis, cell proliferation, apoptosis and it is involved in cancer development. In skeletal muscle, YAP, a downstream target of the Hippo pathway, is an important player in myoblast proliferation, atrophy/hypertrophy regulation, and in mechano-trasduction, transferring mechanical signals into transcriptional responses. We studied components of Hippo pathway in muscle specimens from patients with Duchenne muscular dystrophy (DMD), Becker muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…In addition, myoblast differentiation into myotubes was inhibited by overexpression of mutant YAP that cannot be phosphorylated. The role of YAP deactivation in the further differentiation and maturation of myoblasts into myotubes was further validated by Vita et al (2018), who showed that the lack of skeletal muscle development and regeneration observed in Duchenne muscular dystrophy is associated with inactivation of the Hippo signaling pathway and increased YAP nuclear translocation.…”
Section: Role Of Yap/taz In Myogenic Differentiation and Skeletal Musmentioning
confidence: 93%
“…In addition, myoblast differentiation into myotubes was inhibited by overexpression of mutant YAP that cannot be phosphorylated. The role of YAP deactivation in the further differentiation and maturation of myoblasts into myotubes was further validated by Vita et al (2018), who showed that the lack of skeletal muscle development and regeneration observed in Duchenne muscular dystrophy is associated with inactivation of the Hippo signaling pathway and increased YAP nuclear translocation.…”
Section: Role Of Yap/taz In Myogenic Differentiation and Skeletal Musmentioning
confidence: 93%
“…Yap/Yki together with TEAD/TEF transcription factors regulate the expression of genes that promote cell proliferation, prevent apoptosis, or control innate immunity [29][30][31]. Importantly in mammalian adult skeletal muscles, Yap has been shown to positively regulate skeletal muscle mass and protein synthesis following injury and upon neurogenic muscle atrophy [32] and have differential expression in healthy and dystrophic muscles [33,34]. Recent studies revealed the connection between the DGC and the Hippo pathway in the mouse heart; however, how this interaction influences Hippo and DGC signaling is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…SCs samples were processed in lysis buffer (25 mM Tris/HCL, pH 7.4, 1.0 mM EGTA, 1.0 mM ethylen diamine tetraacetic acid (EDTA), protease, and phosphatase inhibitors) and total proteins concentration was determined using the Bio-Rad protein assay kit (Bio-Rad, Richmond, CA, United States). Integrated density values were expressed as a percentage of densitometric levels using arbitrary densitometric units (Vita et al, 2018).…”
Section: Western Blot Analysismentioning
confidence: 99%